DUKUNGAN KELUARGA DENGAN TINGKAT KEMANDIRIAN LANSIA PASCA STROKE DI POLIKLINIK NEUROLOGI RSU.X - Rumondang Gultom (Jurnal Online Keperawatan Indonesia, 2021)
Post-stroke patients often experience obstacles in Activity Daily Living (ADL), efforts to increase the independence of elderly post-stroke activities require family participation. This study identifies the relationship between family support and the level of independence in Activity Daily Living (ADL) in post-stroke elderly. This study used descriptive correlative with a cross sectional approach. The population in this study were post-stroke patients who visited the Polyclinic of the General Hospital of Sufina Aziz. The research sample was using purposive sampling technique. The research sample consisted of 57 people. Data analysis used Rank Spearman Rho test.This study shows that family support for the level of independence in daily activities in the post-stroke elderly is in the moderate category (54.4%). The level of independence in daily living (ADL) activities in post-stroke elderly in the mild dependency category (73.7%). The results of this analysis meet the criteria of the hypothesis requirements, that there is a relationship between family support and the level of independence in daily living (ADL) activities in post-stroke elderly at RSU Sufina Aziz Medan with a p = 0.014 (p <0.05). Therefore, nurses at the General Hospital Sufina Aziz Medan routinely provide counseling or health education to patients and families about the importance of providing support to the elderly after stroke in Activity Daily Living (ADL).